Joseph Guillaume Desmaisons Dupallans - Cabras, Pier Luigi (Firenze University Press, 2006)
In 1840, a French alienist, or psychiatrist, Joseph Guillaume Desmaisons Dupallans, visited a number of Italian asylums with the objective of discovering the best solution for the institute he was planning to set up in the vicinity of Bordeaux. This book comprises an Italian translation of the notes he made on this trip, conserved in a manuscript in the library of the former psychiatric hospital of San Salvi (Florence). Offering an extremely precise and detailed review of the structures visited, the work is a fascinating and important source for the reconstruction of the history of the institutes for the insane in Italy and also for the history of psychiatry itself.